APLIKASI PUPUK ORGANIK PADAT DAN CAIR DARI KULIT PISANG KEPOK UNTUK PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) - Fadma Juwita Nasution; Lisa Mawarni; Meiriani Meiriani (Jurnal Agroekoteknologi, 2014)
The Application of Solid and Liquid Organic Fertilizer of Banana Kepok Bark on the Growth andYield of Mustard (Brassica juncea L.). The research aimed to know differences in growth responseand yield of mustard in various dose of solid and liquid organic fertilizer from banana kepok barkand the interaction of both factors. The research was carried out in the home screen, Agriculture’sFaculty of North Sumatera University from August to Oktober 2013. The experiment design wasFactorial Randomized Block design (FRB) with two factors and three replications. The first factorwas the solid organic fertilizer dose consist of four levels are 0 , 30 , 60 and 90 g/plant. The secondfactor was a liquid organic fertilizer dose are 0 , 25 , 45 and 65 ml/plant/application. The resultsshowed that the solid organic fertilizer give significant effect on lower the plant height 15 daysafter transplanting and the total of leaf area on 30 days after transplanting. The liquid organicfertilizer significant effect on lower plant height 11 , 19 , 23 , and 27 days after transplanting, dryweight of plant on 30 days after transplanting, the plant yield per sample and yield per plot on 40days after transplanting. The interaction of both significantly on parameter plant height 7 days aftertransplanting and the best result treatment is solid organic fertilizer 30 g/plant without liquidorganic fertilizer.Keywords: Solid Organic, Mustard, Bark of Banana